Impact of viral and host DNA methylations on HPV16-related cervical cancer pathogenesis - Shrinka Sen; Paramita Mandal; Amrapali Bhattacharya; Sudip Kundu; Rahul Roy Chowdhury; Nidhu Ranjan Mondal; Tanmay Chatterjee; Biman Chakravarty; Sudipta Roy; Sharmila Sengupta (Tumor Biology)
Epigenetic alterations within human papillomavirus (HPV) and host cellular genomes are known to occur during cervical carcinogenesis. Our objective was to analyse the influence of (1) methylation within two immunostimulatory CpG motifs within HPV16 E6 and E7 genes around the viral late promoter and their correlation, if any, with expression deregulation of host receptor (TLR9) and DNA methyltransferases (DNMT1, DNMT3A and DNMT3B) and (2) global DNA methylation levels within CpGs of the repetitive Alu sequences, on cervical cancer (CaCx) pathogenesis. Significantly higher proportions of CaCx samples portrayed methylation in immunostimulatory CpG motifs, compared to HPV16-positive non-malignant samples, with cases harbouring episomal HPV16 showing decreased methylation compared to those with viral integration. A significant linear trend of TLR9 upregulation was recorded in the order of HPV–negative controls < HPV16-positive non-malignant samples < HPV16-positive CaCx cases. TLR9 upregulation in cases with episomal HPV16 was again higher among those with non-methylated immunostimulatory CpG motifs. Comparison of cases with HPV–negative controls revealed that DNMT3A was significantly downregulated only among integrated cases, DNMT3B was significantly overexpressed among both categories of cases, although at variable levels, while DNMT1 failed to show any deregulated expression among the cases. Global host DNA hypomethylation, also showed a significant linear increasing trend through the progressive CaCx development stages mentioned above and was most prominently higher among cases with episomal HPV16 as opposed to viral integration. Thus, HPV16 and host methylations appear to influence CaCx pathogenesis, with differential molecular signatures among CaCx cases with episomal and integrated HPV16.